Research of Influence of Blue on Appetite - Wu, Yixuan (Transactions on Environment, Energy and Earth Sciences, 2024)
This essay will analyze the effect of using the color blue to influence appetite and address the rising obesity epidemic. By researching the psychological impacts of color on eating behaviors, it highlights how blue environments can suppress appetite and encourage mindful eating. Historical context shows colors have long influenced moods, with blue promoting relaxation and red stimulating hunger. Research, including studies by Charles Spence and Brian Wansink, indicates that blue, being rare in natural foods, can reduce food consumption. This could be due to evolutionary conditioning and its calming effects. Practical applications in schools, cafeterias, and homes can leverage blue decor to discourage overeating and support healthier eating habits. Although cultural perceptions of color may vary, the current evidence positions blue as a viable, cost-effective tool in public health strategies to combat obesity. Future research should focus on longitudinal studies to better understand the long-term effects of blue environments on eating habits and their potential role in comprehensive weight management programs.